'Delayed' interference effects of air exposure on adult Chinese horseshoe crab Tachypleus tridentatus. (9th September 2019) - Yan, Mingyan; Miao, Fengze; Zhang, Xingzhi; Guo, Haisong; Gul, Yasmeen; Li, Qiongzhen; Song, Jie; Wang, Youji; Hu, Menghong
Abstract: As the haemolymph supplier of the tachypleus amebocyte lysate industry in China, Chinese horseshoe crab ( Tachypleus tridentatus ) inevitably undergoes air‐exposure stress during transportation and haemolymph collection. In this study, the effects of air‐exposure stress and subsequent recovery process on the activities of phosphatases, antioxidant enzymes and haemocyanin concentration in Chinese horseshoe crab were investigated to understand its ability to resist air‐exposure stress. Results showed no significant effects on the total antioxidant capacity (T‐AOC), superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA) and alkaline phosphatase (AKP) between the control and experimental groups during the air‐exposure stress period (0–4 hr), except acid phosphatase (ACP). During the subsequent recovery period in water, significant differences in plasma T‐AOC levels and SOD, CAT, AKP and ACP activities were observed between both groups. No significant effects of CAT activity, SOD activity, MDA content and T‐AOC level were noted between the two groups after 12 hr of recovery. However, the AKP and ACP activities of the experimental group were significantly lower than those of the control group. Results revealed that air exposure may affect the activities of most non‐specific immune enzymes in the plasma of Chinese horseshoe crab, showing a 'delayed" interference effect. Nevertheless, tested antioxidant enzymes have a strong recovery ability and can generally recover to the control group level after 12 hr. Haemocyanin concentration was not affected by air‐exposure stress during the whole experiment. Hereby, Chinese horseshoe crab can strongly resist air‐exposure stress.